Law Enforcement for Perpetrators of Sexual Harassment of Elementary School Students from a Criminal Justice Perspective - Mohammad Irham; Andi Muhammad Rusdi; Hidayati Hidayati (Jurnal Impresi Indonesia, 2024)
The rule of law is applied to perpetrators of sexual harassment against students who will be punished. This study aims to provide a deterrent effect to perpetrators of sexual harassment so as not to do it again, prevent others from doing it, and provide justice to victims of sexual harassment. This research uses a quantitative descriptive approach. Perpetrators of sexual harassment against children in Cimacan State Elementary School, Cianjur Regency are the variables studied. This research has obtained an approval letter from the Cianjur District Education Office. Sampling also involved the parents of the school students. The results showed that the government of the Republic of Indonesia made Law number 23 of 2002 concerning Child Protection to protect children in Indonesia. Articles 46, 47, and 48 of Law No. 23 of 2004 on the Elimination of Domestic Violence regulate law enforcement against perpetrators of sexual abuse against children, including fines and imprisonment for a minimum of three years and a maximum of fifteen years. Several articles in the Criminal Code regulate law enforcement against perpetrators of sexual abuse against children, such as Adultery; Rape; Murder; and Molestation.